Long Noncoding RNA Nuclear Paraspeckle Assembly Transcript 1 Promotes Progression and Angiogenesis of Esophageal Squamous Cell Carcinoma Through miR-590-3p/MDM2 Axis - Luo, Jing; Xie, Kai; Gao, Xiang; Yao, Yu; Wang, Gaoming; Shao, Chenye; Li, Xiaokun; Xu, Yang; Ren, Binhui; Hu, Liwen; Shen, Yi (Frontiers in Oncology, 2021)
Angiogenesis has been identified as one of the hallmarks of cancer and aggravates cancer development and progression. Accumulating evidence indicated that long noncoding RNAs (lncRNAs) are powerful factors in regulating various cancer behaviors. The aim of this study is to verify the function and potential mechanisms of lncRNA NEAT1 in progression and angiogenesis of esophageal squamous cell carcinoma (ESCC). We found that NEAT1 was overexpressed in ESCC tissues and correlated with clinical characteristics of patients. Silence of NEAT1 inhibited proliferation, migration, invasion and angiogenesis of ESCC cells. High throughput sequencing and western blotting revealed that NEAT1 regulated MDM2/p53 pathway. Rescue of MDM2 restored the effect of NEAT1 on progression and angiogenesis of ESCC cells. Nude mice xenograft models further validated the role of NEAT1 in vivo. Importantly, NEAT1 functioned as a competing endogenous RNA for miR-590-3p to regulate MDM2 expression and miR-590-3p acted as a tumor suppressor in ESCC progression and angiogenesis. These findings suggested that NEAT1/miR-590-3p/MDM2 axis might serve as potential therapeutic targets for ESCC patients.